2017
DOI: 10.1037/stl0000077
|View full text |Cite
|
Sign up to set email alerts
|

A review of relationships between item sequence and performance on multiple-choice exams.

Abstract: How best to assess the nature and extent of student learning remains one of the most important issues in large, entry-level psychology courses. Inasmuch as multiple-choice examinations are often used in making that determination, our literature review examined the extent to which item sequence affects performance on such exams. The 2 sequences most commonly included in this body of research are based on item difficulty and conceptual linkage. Considerable research has addressed both possibilities but with mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(81 reference statements)
3
6
0
Order By: Relevance
“…Just as in the first finding, the effect of test anxiety when students face DE and R arranged items may be the reason for the differences in the performance of students in Mathematics. This finding corroborates the result of previous studies such as Soureshjani (2011); Çokluk et al (2016); Hauck et al (2017); Owan et al (2020b), which document that test items arranged in different order affects the performance of students.…”
Section: Discussionsupporting
confidence: 92%
“…Just as in the first finding, the effect of test anxiety when students face DE and R arranged items may be the reason for the differences in the performance of students in Mathematics. This finding corroborates the result of previous studies such as Soureshjani (2011); Çokluk et al (2016); Hauck et al (2017); Owan et al (2020b), which document that test items arranged in different order affects the performance of students.…”
Section: Discussionsupporting
confidence: 92%
“…Just as in the first finding, the effect of test anxiety when students face DE and R arranged items may be the reason for the differences in the performance of students in Mathematics. This finding corroborates the result of previous studies such as Soureshjani (2011);Çokluk et al (2016); Hauck et al (2017); Owan et al (2020b), which document that test items arranged in different order affects the performance of students.…”
Section: Discussionsupporting
confidence: 92%
“…A study documents that an easy-to-difficult (ED) test leads to lower anxiety levels than a difficult-to-easy (DE) test (Çokluk et al, 2016). The argument here is that some studies have documented that test items arranged in different orders affect the performance of students, completion time and items parameters (Balch, 1989;Carlson and Ostrosky, 1992;Çokluk et al, 2016;Hauck et al, 2017;Jessel and Sullin, 1975;Owan et al, 2020a;Picou and Milhomme, 1997;Soureshjani, 2011;Towle and Merrill, 1975). Jessel and Sullin (1975), also found that there is a significant difference in the performance and reliability of tests based on test items arrangement.…”
Section: Introductionmentioning
confidence: 89%